Development Of Health Information Systems For Patient Data Management and Better Care - Ruslan Zuhair Pulungan (International Journal of Health and Social Behavior, 2024)
The development of health information systems (GIS) is important in this digital era to improve patient data management and provide better care. This research aims to develop a SIK that can help health service providers manage patient data more efficiently and improve care coordination. Development steps include requirements analysis, system design, implementation, and performance evaluation. The developed system has features such as recording patient medical history, scheduling appointments, monitoring health conditions, and communication between health care providers. The evaluation results show that the developed SIK succeeded in increasing efficiency in patient data management and care coordination. Healthcare providers can easily access patient information, plan more coordinated care, and communicate effectively with colleagues. Thus, the development of this SIK is expected to make a significant contribution to improving the quality of health services and patient outcomes through better data management and more coordinated care.